Clinical significance of primary tumor progression in metastatic hormone-sensitive prostate cancer - Yasutaka Yamada; Shinichi Sakamoto; Takuya Tsujino; Sinpei Saito; Kodai Sato; Kazuki Nishimura; Tatsuo Fukushima; Ko Nakamura; Yuki Yoshikawa; Tomohisa Matsunaga; Ryoichi Maenosono; Manato Kanesaka; et al. (Prostate International)
Background: Clinical significance of primary tumor progression in patients with metastatic hormone-sensitive prostate cancer (mHSPC) is unclear. Methods: Clinical data from 987 patients with mHSPC from multiple institutions between September 1999 and November 2023 were reviewed. The prognostic impact of primary tumor progression was examined along with other clinical parameters. Castration-resistant prostate cancer progression-free survival (CRPC PFS) and overall survival (OS) were analyzed as clinical outcomes. Student's t-test, Cox proportional hazards models, and Kaplan-Meier methods were utilized to validate the clinical significance. Results: The median age and initial prostate-specific antigen (iPSA) values were 74 and 221 ng/ml, respectively. 632 (64%) and 355 (36%) patients had clinical T stage ≤3 and 4 at diagnosis, respectively. mHSPC patients with clinical T stage 4 were more likely to have a higher grade group (GG), higher frequency of lymph node metastasis, lower hemoglobin (Hb), and more high-volume/risk disease in comparison with those with clinical T stage ≤3. Patients with cT4 were associated with shorter CRPC PFS (P=0.0002) and OS (P < 0.0001). Multivariate analysis identified cT4 as an independent prognostic factor for OS (HR=1.33, P=0.03) along with age, GG, lactate dehydrogenase (LDH), alkaline phosphatase (ALP), albumin (Alb), and high-volume disease. After propensity score matching, patients with cT4 had unfavorable OS in comparison with those with ≤cT3 (P=0.0279). Furthermore, when combined with tumor volume, men with low-volume + cT4 achieved a prognosis comparable to that of patients with high-volume+≤cT3 and high-volume + cT4 (P=0.6876 and P=0.1679, respectively). Conclusion: Bulkiness of primary prostate tumor was associated with worse outcomes in patients with mHSPC. Men with cT4 will require multimodal and intensive therapeutic strategies irrespective of tumor volume.